A new species of Miobdelus Sharp and two new records of Eucibdelus Kraatz (Coleoptera, Staphylinidae, Staphylininae) from China - He, Liang; Zhou, Hong-Zhang (Zootaxa, 2024)
In this paper we describe Miobdelus motuoensis He and Zhou sp. nov. from Xizang, China. Eucibdelus gracilis Kraatz, 1859 and Eucibdelus emawensis Schillhammer, 2023 are reported from China for the first time. Line drawings and color illustrations of adult structures and genitalia are provided for these species.